Toward High Accuracy Positioning in 5G via Passive Synchronization of Base Stations Using Thermally-Insensitive Optical Fibers - Wenwu Zhu; Eric R. Numkam Fokoua; Yong Chen; Thomas D. Bradley; Seyed Reza Sandoghchi; Meng Ding; Gregory T. Jasion; Marco N. Petrovich; Francesco Poletti; Mingshan Zhao; David J. Richardson; Radan Slavik (IEEE Access, 2019)
Positioning accuracy in 5G networks (achieved via techniques based on observed time difference of arrival (OTDoA)) is limited by the synchronization error between the cellular base stations. Here, we demonstrate that these base stations can be synchronized entirely passively through the use of emerging forms of hollow core fiber (HCF) as the data transmission medium in the 5G front-haul network. This is possible due to the excellent thermal stability of HCF which allows the synchronization error among cellular base stations to be reduced significantly as compared to systems based on standard single mode fibers. Reducing this synchronization error is necessary to meet the strict timing requirements envisaged for 5G networks. We analyze the polarization mode dispersion, chromatic dispersion, and thermal stability of the HCF and give suggestions on how to use the HCF to balance overall radio over fiber (RoF) link performance in 5G front-haul networks. In a proof of concept experiment we show that HCF links enable the positioning error (calculated with the OTDoA method) to be reduced down to the centimeter level even when subject to tens of degrees Celsius temperature variations. This represents a 20-fold improvement over standard single mode fiber systems which would require active compensation schemes to achieve similar levels of time synchronization accuracy.